Infective Endocarditis: Current Approaches to Antibacterial Therapy - B. S. Belov; G. M. Tarasova (Антибиотики и Химиотерапия)
The problem of infective endocarditis (IE) continues to maintain its importance because of the high mortality rate and severe complications. Modern IE is a polyetiologic disease, the onset and development of which may be due to the pathogens, components of an extremely extensive list, enlarging almost every year. The serious obstacles in the effective antimicrobial therapy refer to the growing resistance of the IE pathogens to antibiotics and the increasing etiologic role of the previously very rare infectious agents. Timely information of physicians about modern IE treatment methods is of great practical importance. The basic principles of antibiotic therapy of IE with taking into account the latest recommendations of the experts of the European Society of Cardiology (2015) are described.